2012
DOI: 10.2174/1874357901206010104
|View full text |Cite
|
Sign up to set email alerts
|

Application of Molecular Diagnostic Techniques for Viral Testing

Abstract: Nucleic acid amplification techniques are commonly used currently to diagnose viral diseases and manage patients with this kind of illnesses. These techniques have had a rapid but unconventional route of development during the last 30 years, with the discovery and introduction of several assays in clinical diagnosis. The increase in the number of commercially available methods has facilitated the use of this technology in the majority of laboratories worldwide. This technology has reduced the use of some other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
0
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(103 citation statements)
references
References 84 publications
(84 reference statements)
0
98
0
5
Order By: Relevance
“…Only then it was reported that the viral culture from the sample was negative for adenovirus [11]. Even though the virus can disseminate and patients remain infectious for about 2 weeks, the virus can be detected by conventional culture usually in the first 7 days and then the detection rate drops down to 25% by day 10, and at 5-10% by day 14 [13].…”
Section: Viral Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Only then it was reported that the viral culture from the sample was negative for adenovirus [11]. Even though the virus can disseminate and patients remain infectious for about 2 weeks, the virus can be detected by conventional culture usually in the first 7 days and then the detection rate drops down to 25% by day 10, and at 5-10% by day 14 [13].…”
Section: Viral Culturementioning
confidence: 99%
“…All these factors can directly impact the viral recovery rate and thus affect the sensitivity of the viral culture that has been traditionally considered to be the gold standard or reference test [9]. When the reference test is imperfect, the sensitivity and the specificity of an alternative test can be determined by Bayesian LCM statistical analysis which does not assume any test as perfect [13,14]. In this study, the actual sensitivity and specificity of the viral culture, as determined by Bayesian LCM statistical analysis, was 72.2% and 90.8% respectively, although they are traditionally considered to be 100%.…”
Section: Accuracy Of Viral Culturementioning
confidence: 99%
“…The use of molecular methods will also reduce the risk of transmission within the community and health care system nosocomial infections [1,4]. Apart from its health complications, nosocomial infections also cause an increase in the cost of intensive care and prolong hospitalization by weeks or more [4].…”
Section: Detection and Identification Of Nosocomial Infectionsmentioning
confidence: 99%
“…The reasons are based on; the timely advantages, detection of slow growing pathogen or nonculturable organisms that are more or less difficult to detect, identify and even to be test for antimicrobial susceptibility by conventional methods [1][2][3][4][5]. This century is conciding with many highly infectious pathogens, notably HIV AIDS that has been dictating our immune response to the emerging of number of infections [2,3,[6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…They are more sensitive than viral cultures, DFA and Tzanck smears particularly when primers for genes 28 and 29 are used [30,428,429,440,449,450,457] . Molecular biology tests are also useful in the case of varicella appearing 7-42 d after vaccination, in the case of herpes zoster appearing 42 d after vaccination and, in the case of the suspected transmission of the vaccine virus, can distinguish virus vaccine, wild-type virus and potential recombinants of vaccine and wild-type viruses [30,451,452,454,455,[458][459][460][461][462][463] , although some tests have proved to be less appropriate over time for these purposes [30] . There are also some multiplex assays that can differentiate HSV-1, HSV-2 and VZV in cutaneous and mucocutaneous samples, making them very useful in the case of skin lesions of unclear etiology or immunosuppressed patients [429,464,465] .…”
Section: Direct Fluorescent Antibody Assaymentioning
confidence: 99%